PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN INFRASTRUKTUR DI INDONESIA - Fiskia Syafa’ati; Hersugondo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The aim of this paper is to study the impact of working capital management on firm profitability, using the main theoretical framework suggested by the literature. The analyzed companies are infrastructure companies listed on the Indonesia Stock Exchange. The data taken is the company’s financial statement data for the last 5 years. To achieve the research objectives, the researcher used common effect model (CEM) and random effect model (REM).